Clinical use conditions of lead deployment and simulated lead fracture rate in left bundle branch area pacing. (14th February 2023) - Zou, Jiangang; Chen, Keping; Liu, Xingbin; Xu, Yuanning; Jiang, Lingyun; Dai, Yan; Lin, Jinxuan; Hou, Xiaofeng; Qiu, Yuanhao; Himes, Adam; Lucas, Ryan; Demmer, Wade; et al.
Abstract: Introduction: Left bundle branch area pacing (LBBAP) is achieved by advancing the lead tip deep in the septum. Most LBBAP implants are performed using the Medtronic SelectSecure™ MRI SecureScan™ Model 3830 featuring a unique 4 Fr fixed helix lumenless design. Details of lead use conditions and long‐term reliability have not been reported. This study was designed to quantify the mechanical use conditions for the 3830 lead during and after LBBAP implant, and to evaluate reliability using bench testing and simulation. Methods: Fifty bradycardia patients with implantation of the 3830 lead for LBBAP were enrolled. Use conditions of lead deployment at implantation were collected and computed tomography (CT) scans were performed at 3‐month follow‐up. Curvature amplitude along the pacing lead was determined with CT images. Fatigue bending was performed using accelerated testing in a more severe environment than routine clinical use conditions. Conductor fracture rate in a simulated patient population was estimated based on clinical use conditions and fatigue test results. Results: The number of attempts to place the 3830 lead for LBBAP was 2.1 ± 1.3 (range: 1–7) with 13 ± 6 lead rotations at the final attempt. Extreme implant conditions were simulated in bench testing with 5 applications of 20 turns followed by up to 400 million bending cycles. Reliability modeling predicted a 10‐year fracture rate of 0.02%. Conclusions: LBBAP implants require more lead rotations than standard pacing implants and result in unique lead bending. Application of simulated LBBAP use conditions to the 3830 lead in an accelerated in‐vitro model does not produce excess conductor fractures. IMAGE‐LBBP Study ID of ClinicalTrial.GOV: NCT04119323.